Afghanistan Renewable Energy Development Issues and Options - World Bank Group (World Bank, Washington, DC, 2018)
Afghanistan is facing many economic and political challenges as it deals with spreading insurgency, declining economic growth, and continuing poverty. The government is working on a number of fronts to stimulate economic activity through its own initiatives and in partnership with International Development Organizations but will continue to be challenged in the near and medium term as a growing population seeks jobs and business opportunities. One of the initiatives that the Government of Afghanistan (GoA) has identified is to capitalize on its wealth of Renewable Energy (RE) resources with a view to both increasing the delivery of electricity services to the population and developing domestic business opportunities both directly linked to RE technology and linked to improved access to reasonably priced electricity. The objective of this paper is to review the potential viability of RE as part of the country’s electricity supply plan, and at the same time to identify issues that might hinder or even derail the process.